Relationship between TQM Elements and Organizational Performance (Pakistan Journal of Commerce and Social Sciences (ISSN 1997-8553), 2013)
This study empirically reveals the influence of the TQM elements comprising leadership, people management, process management, customer focus, information & analysis and strategic planning on the organizational performance in the manufacturing sector of Pakistan. The data were collected through a questionnaire survey from the 160 managers and employees of the manufacturing firms. Results using SPSS support the hypotheses that there is a positive relationship between the TQM elements and performance of Pakistani manufacturing firms. Furthermore, it is also found that customer focus is perceived as a dominant TQM practice for enhancing quality performance. Moreover, this study also provides a valuable knowledge to the top managers. Practical implementations along with the limitations have also been discussed in this study.